2007
DOI: 10.1088/0031-8949/76/5/019
|View full text |Cite
|
Sign up to set email alerts
|

Study of a bounded oscillator problem in one dimension

Abstract: In this paper, we have studied the bounded oscillator potential for the Schrö dinger equation with the asymptotic iteration method (AIM). This work introduces a simple perturbation expansion and a new analytical expression for the energy eigenvalues. Our results have been compared with those obtained from the direct application of the AIM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…In this paper, the asymptotic iteration method (AIM), which has been proposed by Ciftci et al [34][35][36][37][38][39] in recent years, has been applied to solve the N-dimensional non-relativistic Schrödinger equation for diatomic molecules. This method of solution, based on solving the second-order homogeneous linear differential equations, has been used to solve one-, two-and three-dimensional Schrödinger equations for central potentials [38,[40][41][42]. The solutions of the Klein-Gordon equation with the generalized Hulten and Kratzer potential in D dimensions have been investigated with the AIM by Saad [43] and Saad et al [44], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the asymptotic iteration method (AIM), which has been proposed by Ciftci et al [34][35][36][37][38][39] in recent years, has been applied to solve the N-dimensional non-relativistic Schrödinger equation for diatomic molecules. This method of solution, based on solving the second-order homogeneous linear differential equations, has been used to solve one-, two-and three-dimensional Schrödinger equations for central potentials [38,[40][41][42]. The solutions of the Klein-Gordon equation with the generalized Hulten and Kratzer potential in D dimensions have been investigated with the AIM by Saad [43] and Saad et al [44], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The use of 10 or 20 terms in the potential series instead of 2 or 3 caused no essential difficulty for the method, except that it became necessary to perform an extra check on the convergence of the results as the number of potential terms used was increased. Thus the method should also be applicable (at least for sufficiently large R values) to the potential x 2 /(1x 2 /R 2 ) 2 , which was treated by means of the AIM approach in a recent work [24].…”
Section: Discussionmentioning
confidence: 99%
“…The approach just mentioned was mainly applied to quantum-mechanical models with asymptotic boundary conditions at infinity [1][2][3][4][5][6][7][8][9][10][11], but it was suggested that it may be suitable for bounded problems as well [8]. In this paper, we try the RPM on the bounded anharmonic oscillator recently discussed by Ciftci and Ateser [12] that may be suitable for the study of quarkonium physics.…”
Section: Introductionmentioning
confidence: 99%
“…In secion 2, we outline the main features of the RPM. In section 3, we apply the RPM to the bounded oscillator proposed by Ciftci and Ateser [12]. In section 4, we briefly address the problem of spurious roots.…”
Section: Introductionmentioning
confidence: 99%